2021
DOI: 10.47752/sjss.42.59.64
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of E-Learning Systems on Information Overload and Social Media Addiction During the Covid-19 Pandemic

Abstract: Objective: This paper investigates the association of information overload and social media addiction with academic attainment among a sample of college students in Kuwait as they switched from face-to-face to e-learning systems during the COVID-19 pandemic. The closure of universities and colleges made this a mandatory transition. Educators posit information overload (IO) would increase due to the ease of creating, sharing, and duplicating information through social media platforms. Method: This cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This drew students' attention to the pandemic. A similar study by Alali et al (2021) and Alheneidi et al (2021) in Kuwait Universities revealed that 54% of students had heard of COVID-19. In the same study, the major source of information was social media.…”
Section: Heard Of Covid-19mentioning
confidence: 67%
“…This drew students' attention to the pandemic. A similar study by Alali et al (2021) and Alheneidi et al (2021) in Kuwait Universities revealed that 54% of students had heard of COVID-19. In the same study, the major source of information was social media.…”
Section: Heard Of Covid-19mentioning
confidence: 67%
“…Perceived information overload, especially in the realm of social media, not only induces negative emotional states but can also precipitate adverse behavioral responses, as noted by Luqman et al 36 Moreover, empirical investigations have substantiated a correlation between information overload and internet addiction, as evidenced by the research conducted by Alheneidi. 37 In a previous study, Alheneidi et al 38 ascertained that excessive exposure to information on social media platforms resulted in heightened stress among users and could ultimately lead to exhaustion. Additionally, analysis of data from 405 WeChat users and 442 smartphone app users demonstrated that information overload and communication overload exert a positive influence on users’ exhaustion.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Information overload (IO) is a stress-related syndrome resulting from an excessive amount of information (AlHeneidi et al, 2021). This typical feature of today's workplace is caused by the rapid advancement of information and communication technologies, a trend further accelerated by the COVID-19 pandemic (Mannion, 2022).…”
Section: Information Overload and The Effect On Burnoutmentioning
confidence: 99%
“…Faced with the avalanche of information from diverse sources, employees find it challenging to manage the influx, leading to "information fatigue syndrome" (Buchanan & Kock, 2001) which affects a person's ability to distinguish, categorize, organize, process, and learn from new information (Nowak et al, 2018). Excessive information has been linked to work-related stress, irritation, agitation, and depression (Alheneidi & Smith, 2021). Moreover, it unfavorably affects decision-making, innovative thinking, productivity, and motivation (Nowak et al, 2018), which can disturb workplace dynamics and negatively affect individual well-being.…”
Section: Information Overload and The Effect On Burnoutmentioning
confidence: 99%